The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1139/cjm-2012-0352
|View full text |Cite
|
Sign up to set email alerts
|

Brassica napus polygalacturonase inhibitor proteins inhibit Sclerotinia sclerotiorum polygalacturonase enzymatic and necrotizing activities and delay symptoms in transgenic plants

Abstract: Sclerotinia sclerotiorum releases a battery of polygalacturonases (PGs) during infection, which the host plant may cope with through production of polygalacturonase inhibitor proteins (PGIPs). To study the interaction between S. sclerotiorum PGs and Brassica napus PGIPs, 5 S. sclerotiorum PGs and 4 B. napus PGIPs were expressed in Pichia pastoris. SsPG3, SsPG6, and BnPGIP1 were successfully produced in the yeast system, and BnPGIP1 inhibited SsPG6 enzymatic activity in vitro. SsPG3 and SsPG6 both induced light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…During Phaseolus vulgaris infection, SsPG1 is induced during the later stages of the interaction (48-72 hpi), SsPG 3 is up-regulated earlier at 12 hpi, while SsPG6 exhibits a bimodal pattern with peaks of expression at 6 and 48 hpi [40]. SsPG3 and SsPG6 are also potent inducers of light-dependent necrotic reactions [54]. Similarly, B. cinerea BcPG1 and BcPG2 exhibit strong necrosis-inducing activity [55] and deletion of either gene reduces B. cinerea virulence [55, 56].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During Phaseolus vulgaris infection, SsPG1 is induced during the later stages of the interaction (48-72 hpi), SsPG 3 is up-regulated earlier at 12 hpi, while SsPG6 exhibits a bimodal pattern with peaks of expression at 6 and 48 hpi [40]. SsPG3 and SsPG6 are also potent inducers of light-dependent necrotic reactions [54]. Similarly, B. cinerea BcPG1 and BcPG2 exhibit strong necrosis-inducing activity [55] and deletion of either gene reduces B. cinerea virulence [55, 56].…”
Section: Resultsmentioning
confidence: 99%
“…In the S. sclerotiorum- A. thaliana interaction, SsSSVP1 showed significant up-regulation starting from 3 hpi and slowly increased from 6 to 12 hpi [155], suggesting that the expression pattern of this gene could be host-dependent. As noted above, several hydrolytic enzymes, including certain polygalacturonases [54, 55] and xylanses [57], are also potent inducers of host necrosis.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, silencing of their expression using an antisense Atpgip , led to enhanced susceptibility (Ferrari et al, 2006 ). Arabidopsis plants expressing Pvpgip2 , encoding an efficient inhibitor of the B. cinerea PG (ten Have et al, 1998 ), showed reduction of disease symptoms caused by B. cinerea and those expressing the rapeseed genes Bnpgip1 and Bnpgip2 delayed the symptoms caused by S. sclerotiorum (Bashi et al, 2013 ).…”
Section: Pgips Engineered In Dicot Cropsmentioning
confidence: 99%
“…Following cuticle penetration, a short biotrophic phase allows the pathogen to establish within the host (Kabbage et al 2015). Mycelia then ramify throughout host tissue, assisted by the release of hydrolytic enzymes (Martel et al 1996;Poussereau et al 2001a, b;Kasza et al 2004;Li et al 2004;Bashi et al 2012;Zhang et al 2014), oxalic acid (Godoy et al 1990) and necrosis-inducing proteins (Bashi et al 2010a;Bashi et al 2013). Consumption of necrotic host tissue provides the resources needed for sclerotial development and completion of the life cycle.…”
Section: Introductionmentioning
confidence: 99%